2007
DOI: 10.1007/s11249-007-9242-9
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Magnetic Tape/Guide Friction Reduction by Laser Surface Texturing

Abstract: The friction coefficient between a magnetic tape and a guide in a tape path can be minimized by creating micro dimples on the guide surface with laser surface texturing. The dimples enhance the formation of an air bearing and reduce the friction coefficient between the tape and the guide due to the increased spacing. A model is presented to optimize the geometry of the surface texturing parameters to maximize the average air bearing pressure and minimize the tape/guide friction coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The preferred and most efficient way to optimize surface texturing is by parametric analysis in a theoretical model. This was done in several models for bearings [18,29], various seals [8,11,13,23,24,31], piston rings [14,26] and magnetic recording tapes [32] to obtain maximum load capacity, minimum friction, maximum film stiffness and minimum leakage. Many experimental studies attempting optimization by trial and error approach can also be found in the literature (see Ref.…”
Section: Optimizationmentioning
confidence: 99%
“…The preferred and most efficient way to optimize surface texturing is by parametric analysis in a theoretical model. This was done in several models for bearings [18,29], various seals [8,11,13,23,24,31], piston rings [14,26] and magnetic recording tapes [32] to obtain maximum load capacity, minimum friction, maximum film stiffness and minimum leakage. Many experimental studies attempting optimization by trial and error approach can also be found in the literature (see Ref.…”
Section: Optimizationmentioning
confidence: 99%
“…As the clearance h 0 decreases from 0.28 to 0:028 lm, 0:0028 lm, or 0, the pressure rise over the converging region of the dimple and the pressure drop over the diverging region become intense, and the pressure rise becomes greater than the pressure drop. In previous theoretical studies [9,10], the generation of high average gas pressure has been explained as resulting from this asymmetric pressure distribution over the dimple region in the case of gas lubrication using surface texturing as well as in the case of liquid lubrication.…”
Section: Mechanism Of High Gas Pressure Generationmentioning
confidence: 99%
“…They investigated the optimal conditions to improve sealing performance by changing the values of parameters, e.g., seal clearance, dimple area density, and dimple aspect ratio. Other parametric analyses have been conduced to investigate optimal conditions of gas lubrication with surface texturing [9,10]. However, a clear understanding of the mechanism that induces high gas pressure over a textured surface would help us to design the optimal configuration of the surface texture without trial and error.…”
Section: Introductionmentioning
confidence: 99%
“…4b-d. Talke and colleagues [29,30] studied the phenomenon of reducing the friction coefficient between the magnetic tape surface and the guide interface by laser surface texturing (LST) and put a mathematical model that predicts the optimum dimensions for these induced microdimples on the surface that gives the lowest friction coefficient. Current results showed that the existence of such lubricant aggregates or micro-dimples, with some specific geometry and distribution intensity, on the magnetic tape surface resulted in reducing the friction coefficient the same way if they were existed on the guide interface via LST.…”
Section: Surface Topography and Optical Imaging Of The Representativementioning
confidence: 99%
“…These micro-dimples act as micro-hydrodynamic bearings, thereby creating a local pressure increase between the sliding surfaces [29,30]. This in turn increases the load carrying capacity for such bearings and reduces the friction coefficient for a constant load.…”
Section: Microtribological Behavior and The Micro-dimples Modelmentioning
confidence: 99%